ASSESSING THE IMPACT OF RESISTANCE TRAINING AND WEIGHT TRAINING ON SPEED AND STRENGTH IN FEMALE HANDBALL PLAYERS - K, Sujatha; K.P, Habeebu Rehman; B., Krishna Deepika (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study investigates the impact of resistance training (RT) and weight training (WT) on speed and strength in female handball players. Handball requires a combination of strength, power, speed, and endurance, and enhancing these physical attributes through targeted training programs is crucial for improving performance. The study involved 60 female handball players aged 1825 who are represented in National Level Competitions randomly assigned to a control group (CG), a resistance training group (RTG), and a weight training group (WTG). Over 12 weeks, RTG and WTG participated in structured training, while CG maintained their usual routines. Pre- and post-tests measured strength and speed, with adjustments made for initial differences using ANCOVA. Results showed that both RT and WT significantly increased strength compared to the CG, with the RTG exhibiting the greatest improvement. While speed improvements were less pronounced, both training groups displayed significant enhancements in speed relative to the control group, although no substantial difference was found between RT and WT in terms of speed improvement. The findings suggest that both RT and WT are effective for enhancing strength in female handball players, with moderate improvements in speed, providing valuable insights for optimizing training programs in female handball athletes.